2003
DOI: 10.1590/s0021-75572003000400008
|View full text |Cite
|
Sign up to set email alerts
|

Uso de chupeta e sua relação com o desmame precoce em população de crianças nascidas em Hospital Amigo da Criança

Abstract: The use of pacifiers is deeply rooted in our culture, even in a population oriented towards avoiding it. The association between pacifier use and shorter duration of breastfeeding and exclusive breastfeeding was confirmed in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
70

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(104 citation statements)
references
References 11 publications
4
30
0
70
Order By: Relevance
“…Other reflections are necessary about the use of artificial nipples, because they have been described in the literature as a factor that contributes to weaning and that, in the current study, presented a statistically significant association with weaning in all ages; a result that was also observed in other studies (15,27,28) .…”
Section: Discussionsupporting
confidence: 87%
“…Other reflections are necessary about the use of artificial nipples, because they have been described in the literature as a factor that contributes to weaning and that, in the current study, presented a statistically significant association with weaning in all ages; a result that was also observed in other studies (15,27,28) .…”
Section: Discussionsupporting
confidence: 87%
“…Diversos estudos têm mostrado uma associação inversa entre o uso de chupeta e o aleitamento materno [23][24][25] . Um possível mecanismo seria a redução da freqüência das mamadas diárias, o que poderia levar à baixa estimulação da mama e à conseqüente diminuição da produção de leite 26 .…”
Section: Discussionunclassified
“…However, its mechanism of action remains unclear. 24 Some authors suggest that the use of pacifier may lead to early weaning 15 , whereas others believe that it is the early termination of exclusive breastfeeding that leads to the use of pacifiers 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Among infants born at a Child-Friendly Hospital, it was found that 61.6% used pacifiers at the end of the first month of life. 15 Mascarenhas et al 16 suggest that, although the population is instructed to avoid the use of pacifiers, we should consider that its use is a cultural habit that is difficult to control and eradicate. Therefore, it is possible to affirm that the institutional rules (that try to discourage the use of pacifiers by using a professional and scientific rhetoric) are not achieving their goals because they collide with the beliefs of the women served by the program, who disregard prohibitions and maintain their reasons for offering this device 17 .…”
Section: Discussionmentioning
confidence: 99%